Crafting and Testing an Elementary Device for Transporting U Ditches for Hands-on Learning in Road and Bridge Engineering at Technical High Schools - Ratna Putri, Mukhlisya Dewi; Mursid, Mursid (Jurnal Fondasi, 2024)
This research aims to develop a simple and effective tool for moving U- shaped drainage channels (U ditch) with the aim of helping construction workers and farmers move U ditch more easily and efficiently. For this reason, this research takes the title "Development and Evaluation of a Simple Tool for Moving U Ditch as a Practice Tool for Vocational Engineering Students in Road and Bridge Design”. This research also provides practical training facilities for road and bridge design engineering vocational students. The research method used is to make prototypes of tools from materials that are durable and easily available, and then tested in the field. The research results show that the developed tool can increase effectiveness and efficiency in moving U ditch at low cost. It is hoped that this research can contribute to the development of better and more innovative construction technology. From all the processes carried out, this research is classified as TKT scale 3 with a national research focus area of Engineering Engineering which has a national research priority for 2020 - 2024 to produce added value. It is hoped that the indicators in the TKT 3 categories can be met, from the methodological design used to answer the research questions that has been prepared to producing a simple tool design for moving u-ditch for practical learning. The scientific publications that can be produced from this research include the Accredited National Journal : SNIV Journal.